A numerical model of a red blood cell infected by Plasmodium falciparum malaria: coupling cell mechanics with ligand-receptor interactions. Issue 1 (1st December 2016) - Ishida, Shunichi; Imai, Yohsuke; Ichikawa, Yuki; Nix, Stephanie; Matsunaga, Daiki; Omori, Toshihiro; Ishikawa, Takuji
Abstract : We developed a numerical model of the behavior of a red blood cell infected by Plasmodium falciparum malaria on a wall in shear flow. The fluid and solid mechanics of an infected red blood cell ( Pf -IRBC) were coupled with the biochemical interaction of ligand-receptor bindings. We used the boundary element method for fluid mechanics, the finite element method for membrane mechanics, and the Monte Carlo method for ligand-receptor interactions. We simulated the behavior of a Pf -IRBC in shear flow, focusing on the effects of bond type. For slip bonds, the Pf -IRBC exhibited firm adhesion, tumbling motion, and tank-treading motion, depending on the applied shear rate. The behavior of catch bonds resembled that of slip bonds, except for a 'catch' state at high shear stress. When the reactive compliance decreased to a value in the order of10 - 2 nm, both the slip and catch bonds behaved like an ideal bond. Such bonds do not respond to the force applied to the bond, and the velocity is stabilized at a high shear rate. Finally, we compared the numerical results with previous experiments for A4- and ItG-infected cells. We found that the interaction between PfEMP1 and ICAM-1 could be a nearly ideal bond, with a dissociation rate ranging from30 s - 1 to100 s - 1 . Graphical Abstract: